2013
DOI: 10.1371/journal.pone.0083596
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Transfection of Mouse and Human Neural Stem Cell Cultures

Abstract: The use of synthetic mRNA as an alternative gene delivery vector to traditional DNA-based constructs provides an effective method for inducing transient gene expression in cell cultures without genetic modification. Delivery of mRNA has been proposed as a safer alternative to viral vectors in the induction of pluripotent cells for regenerative therapies. Although mRNA transfection of fibroblasts, dendritic and embryonic stem cells has been described, mRNA delivery to neurosphere cultures has not been previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Taken the transfection efficiency and MFI of the GFP positive cells into consideration, the ratio of N/P of 5 was selected for future studies. The difference between the percentage of transfected cells and the MFI of transfected cells was consistent with previously reported results ( McLenachan et al, 2013 ; Avci-Adali et al, 2014 ; Lee et al, 2015 ; Li et al, 2017a ). Transfection using the same transfection reagent led to similar transfection efficiency but not the MFI ( Figures 4D,E ) with the increase of the incubation time, which was consistent with previously report ( Avci-Adali et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…Taken the transfection efficiency and MFI of the GFP positive cells into consideration, the ratio of N/P of 5 was selected for future studies. The difference between the percentage of transfected cells and the MFI of transfected cells was consistent with previously reported results ( McLenachan et al, 2013 ; Avci-Adali et al, 2014 ; Lee et al, 2015 ; Li et al, 2017a ). Transfection using the same transfection reagent led to similar transfection efficiency but not the MFI ( Figures 4D,E ) with the increase of the incubation time, which was consistent with previously report ( Avci-Adali et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, the outermost stratum corneum layer of the epidermis serves as a tight barrier to the absorption of topically administered drugs [97]. Heretofore, various approaches have been adopted to overcome this barrier, including physical (e.g., microporation [98], microneedles [99], and jet injection [100,101]), active (e.g., electroporation [102], iontophoresis [103], and sonophoresis [104]), and passive methods (e.g., nanoparticles [105] and liposomes [106]). Electroporation and sonoporation can transiently permeabilize the skin by means of electric pulses and low-frequency ultrasound, respectively, for efficient delivery of genes into the skin [107].…”
Section: Naked Rnamentioning
confidence: 99%
“…Therefore, for subsequent experiments, this copy number was used for double transfection (multifection) in order to yield maximal gene transfer. Double transduction/transfection is routinely used for many viral as well as non-viral genetic modification approaches such as lipid-mediated gene delivery and electroporation in order to enhance transfection efficiency and to prolong gene expression [37][38][39]. We previously showed that multifection of NSCs (cultured as 3-D neurospheres) resulted in higher transfection levels (~27%) compared to single transfection (~13%) with no effect on cell physiology and health [22].…”
Section: Minicircle Use With Magnetofection Dramatically Enhances Nscmentioning
confidence: 99%